Computing Performance: Game Over or Next Level? - Fuller, Samuel H.; Millett, Lynette I. (Computer (00189162), 2011)
The end of dramatic exponential growth in single-processor performance marks the end of the dominance of the single microproessor in computing. The era of sequential computing must give way to an era in which parallelism holds the forefront. Although important scientific and engineering challenges lie ahead, this is an opportune time for innovation in programming systems and computing architectures.